An alternative minimally invasive technique for genetic sampling of bats: Wing swabs yield species identification - Delanie Player; Cori Lausen; Beryl Zaitlin; Jori Harrison; David Paetkau; Erin Harmston (Wildlife Society Bulletin)
ABSTRACT Bat species are traditionally identified morphologically, but in some cases, species can be difficult to differentiate. Wing punches (biopsies) of wing or tail membranes are commonly used to collect tissue for DNA analysis, but less invasive techniques are preferable. As such, DNA acquired using buccal and wing swabs or from fecal pellets are increasingly being employed. We compared a dry swabbing technique with the wing biopsy technique for DNA collection. We compared species identification between tissue biopsies and wing swabs collected from bats in Alberta and British Columbia, Canada, between April and November, 2014, and September and October 2015. Species identification was achieved with varying methods of field collection and lab processing. DNA was extracted, sequenced, and compared with reference sequences and field identifications. We concluded that wing swabs are an effective way to identify bat species genetically and far less invasive than biopsy techniques. These methods should be considered for genetically sampling bats, especially during seasons when wounds from biopsy are slow to heal. © 2017 The Wildlife Society.